Intergroup dialogue facilitation training and faculty cultural competence - Howard, Sepopo V. (My University, 2023)
The current investigation evaluated faculty cultural competence in two studies; Study 1 included qualitative interviews with faculty who had and had not been trained in IGD, while Study 2 examined student perceptions of the cultural competence of faculty from Study 1. Differences in how faculty see themselves in the classroom were explored and it was hypothesized that students would rate faculty who had been trained in IGD higher on a measure of cultural competence than faculty who had not. Study 1 revealed several themes from thematic analyses of faculty participant responses. Results from Study 2 indicated that students perceived faculty who had been trained in IGD as having greater cultural competence than faculty with no IGD experience. Findings of this study highlight the importance of student perceptions and suggest that training in Intergroup Dialogue methodology is a promising avenue to build knowledge, awareness, skill, approachability, and cultural competence among faculty.
(M.A.) -- Towson University, 2019